Translation as Listening and Encounter with the Other in Migration and Globalization Processes Today - Petrilli, Susan; Ponzio, Augusto (TTR)

(untitled) (Association canadienne de traductologie, 2006)
AbstractTranslation is viewed from a semiotic perspective with a special focus on translator discourse genre and the different forms of reported discourse. The distinction between listening and wanting to hear and between silence and taciturnity is introduced to analyze the relation between translation and understanding, translation and the other, translation and hospitality, with special reference to the problematic of migration and globalization processes today. This leads to considerations on the ethical character of translation understood as listening, therefore on the responsibilitry of the translator towards the other in the encounter between different signs, languages, and cultures. The translator is called to account to and for the other. Given that translation must ultimately acknowledge the rights of others, the responsibility of the translator may be qualified as “semioethic responsibility.’